Conselhos escolares: avaliação da política de gestão democrática escolar em Maracanaú no Ceará - Guimarães, Vanessa Rocha de Santana (2024)
This research aims to evaluate the performance of the School Councils of Maracanaú, analyzing their possibilities and challenges for the effectiveness of Democratic Management in municipal public schools of Early Childhood Education and Elementary School. Our objective is to analyze the context and content of the School Councils Policy, investigating their trajectories and seeking to understand the performance of the counselors in the time frame of 5 years (2019-2023) and territorial, considering the municipality of Maracanaú. Understanding that the school is configured as an important ally in the confrontation of social inequalities in Brazil, having as a social function to form ethical, critical and participatory citizens, we understand and affirm that to comply with such designs, it must find support in the School Council as a management tool that brings together the entire school community in a representative way. This research is characterized by the qualitative approach in its typology, in which we use the bibliographic analysis, documentary and field research; among the essential authors in their contributions and reflections on conceptions of Education for our research, we highlight: (Gonh, 1990, 2002, 2004; Schwarcz, 2020; Paro, 2001, 2017; Vieira, 2002, 2012; Luck, 2012; Libâneo, 2004; Barcelar, 2003; Cury, 1992, 2010) ; we also used the in-depth evaluation of the policy proposed by Rodrigues (2016, 2011, 2008). Therefore, we established the triangular analysis of the information collected in the document analysis, with the questionnaire applied and interview collected, generating subsidies for the evaluation of the policy object of the research. As a result, we can see that there is a belief in the importance of school boards, but there is still misinformation about the role of board members. Nevertheless, there is a considerable amount of legislation, however the effective functioning of the councils is still dependent on the awareness of the management nuclei. The trainings are a fundamental role in trying to correct the failures of implementation of the policy, however they still suffer from the impact of the COVID-19 pandemic and the absence of time to organize the entire school agenda. In short, the research broadened the vision of a policy that faced and faces difficulties, but that promises the democratic construction of education.